Kárpátalja vasúthálózatának alakulása az 1939-es területvisszacsatolás következtében - Miszlay, Zsolt (Közép-Európai Közlemények, 2010)
After the decision of Trianon the Hungary’s area and railway’s network were grown by the decisions of Vienna in 1938 and 1940, further the Sub-Carpathia recovery in 1939 and Délvidék recovery in 1941. The World War Two’s federal system and the military and political situation bringing to Hungary’s role, and this case row got to the first Vienna decision in 2th November 1938. In this decision case Hungary got with the highlands areas together 1042 km normal, and 42 km a narrow track gauge railway line. In the spring of 1939 were the next area revision In Kárpátalja, and Hungary got back and made new normal, and narrow track gauge railway line. This following the second Vienna decision on 30. 08. 1940, and it were feedback Észak Erdély and Székelyföld to Hungary. In this decision case Hungary got 1860 km normal, and 423 km a narrow track gauge railway line. Beetween the world wars, the last moment were the occupation of the Délvidék, and the Hungarian ralwys grown 12742 km long. This study presentation the Sub-Carpatian situation around 1930–1940.